A retrospective study on factors associated with COVID-19 vaccine refusal among individuals aged 15 years and above in the general population of Bamenda I sub-division, Cameroon - Cédric, Yamssi; Nadia, Noumedem Anangmo Christelle; Chewah, Abongwa Delight; Liu, Wenjuan; Liu, Ye; Kevin, Tako Djimefo Alex; Payne, Vincent Khan; Hu, Haibo (Frontiers in Public Health, 2025)
BackgroundBy the end of 2020, several vaccines aimed at combating COVID-19 were authorized for widespread immunization. The aim of this study was to assess the factors that were associated with COVID-19 Vaccine refusal in Bamenda I.MethodThis was a retrospective study carried out in the subdivision of Bamenda I, from March to June 2024, through interviews and questionnaires in which participants were asked to recall important events during the COVID-19 pandemic. A questionnaire-based survey was conducted to ensure diverse representation in the community study. The questionnaire comprised four sections: socio-demographic characteristics, knowledge about COVID-19 and vaccines, attitudes toward COVID-19, and beliefs about the vaccine. Data were collected during community gatherings, such as focus group discussions and training sessions, and also through Google Forms via the Kobo tool for participants with Android phones. Data were then transferred to SPSS for analysis, using the Pearson chi-square test to examine associations, with p-values <0.05 deemed significant.ResultsOur results show that 42.40% participants had high knowledge about COVID-19, 39.40% had moderate knowledge while 18.20% had low knowledge. Their vaccination status, showed that, just 12.10% were vaccinated, and 87.90% were unvaccinated. Socio-demographic factors like age, gender, and education recorded significant associations with respect to vaccine refusal p-value < 0.05. Participants of the study (80.8%) were concerned about the potential side effects of vaccines, while 19.2% said they were not. Some participants (53.5%) mentioned that vaccines were not necessary now that the pandemic has slowed down, while 43.5% disagreed. When asked if they will advise their family and friends to get vaccinated, 9.1% strongly agreed, 21.2% agreed, 40.4% were neutral, 17.2% disagreed, and 12.1% strongly disagreed. A total of 17.2% had underlying health conditions which prevented them from receiving the vaccine while 82.8% had no underlying health conditions. Many believed that the vaccines were promoted for financial reasons. Also, when asked if they knew some preventive measures of the disease, 17.2% said taking COVID-19 vaccine could help in prevention, 13.1% said hand washing could help, 17.2% said wearing of nose masks, 14.1% believed herbal remedies were most suitable and a majority, 38.4% believed in the combination of all of the above measures to prevent the disease.ConclusionThe study highlights significant knowledge gaps and widespread concerns about vaccine safety among the population in Bamenda I, indicating a need for targeted educational interventions to improve vaccination rates.